UNDERWEIGHT, OVERWEIGHT, GENERAL AND CENTRAL OBESITY IN 5-YEAR-OLD CHILDREN FROM NORTH MACEDONIA - Zafirova, Biljana; Chadikovska, Elizabeta; Trpkovska, Biljana; Stojanoska, Biljana Bojadzieva; Dodevski, Ace (Journal of Morphological Sciences, 2022)
The objective of this study is to investigate the distribution of underweight, overweight, and the general and central obesity in 5-year-old children from North Macedonia, through the use of the anthropometric indices, BMI for general and WHR for central or abdominal obesity. In this study, a total of 248 children (124 boys and 124 girls) are investigated. Anthropometric indicators are measured using a standard protocol. We select four parameters to measure (weight and height) and two circumferences (waist WC and hip HC). The following indices are taken into consideration: Body mass index (BMI) and waist-to-hip ratio (WHR). The percentile distribution of the tested variables was done by gender. Some anthropometric parameters (weight, height, and BMI) have shown significant sex-specific differences in favour of boys, with exception of circumference and WHR. Overweight occurs in 5.65% of the boys and 12.1% of the girls, and obesity occurs in 10.48% of boys and 4.84% of the girls. The underweight is 4.84 % of the boys and 5.64% of the girls. Central or abdominal obesity across cut-off points (WHR and WC-for-age >=90th percentile) occurs in 13.7 % and 12.9 % of the boys and 12.1 % and 10.48% of the girls respectively.  Central obesity, as well as general obesity, is more frequent in boys than girls. These results and the determination of BMI, WC, and WHR cut-off values can be used for estimating underweight, overweight, general, and central obesity and consequences associated with it in children aged 5 years from North Macedonia.  Keywords : BMI, WC, WHR, children, overweight, central obesity, underweight. https://doi.org/10.55302/JMS2251119z